2020
DOI: 10.3389/fphys.2020.00975
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Cytoskeleton-Associated Role of PDLIM5

Abstract: Regenerative medicine represented by stem cell technology has become one of the pillar medical technologies for human disease treatment. Cytoskeleton plays important roles in maintaining cell morphology, bearing external forces, and maintaining the effectiveness of cell internal structure, among which cytoskeleton related proteins are involved in and play an indispensable role in the changes of cytoskeleton. PDLIM5 is a cytoskeleton-related protein that, like other cytoskeletal proteins, acts as a binding prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 81 publications
0
31
0
Order By: Relevance
“…6a). This approach nominated PDLIM5, a member of cytoskeletonassociated protein family 35 , as a robust target of this HNRNPC-mediated pathway.…”
Section: Pdlim5 Acts Downstream Of Hnrnpc To Suppress Metastasismentioning
confidence: 99%
“…6a). This approach nominated PDLIM5, a member of cytoskeletonassociated protein family 35 , as a robust target of this HNRNPC-mediated pathway.…”
Section: Pdlim5 Acts Downstream Of Hnrnpc To Suppress Metastasismentioning
confidence: 99%
“…As an actin connector protein, PDLIM5 is not only involved in cytoskeletal tissue, cellular processes and organ development but is also presumed to be involved in the genesis and development of tumors 27 . PDLIM5 has been reported to play an important role in a variety of cancers, including papillary thyroid cancer, prostate cancer and non-small cell lung cancer [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…PDLIM5 is a cytoskeleton-related protein that acts as a binding protein [22]. In neurons, PDLIM5 has been found that present at both presynaptic and postsynaptic sites [34,35].…”
Section: Discussionmentioning
confidence: 99%